Edukasi Perilaku Hidup Bersih Dan Sehat (Phbs) Dalam Pencegahan Covid-19 Kepada Kader Posyandu Mawar Desa Palioi Kecamatan Kindang Kabupaten Bulukumba - Anita Anita; Risnawaty Alyah; Bambang Ariyanto (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2020)
The latest threat in the world of global health is an outbreak of a respiratory disease known as Coronavirus Disease 2019 (C ovid-19). This disease is transmitted by droplets when talking, coughing and sneezing from an infected person with the Coronavirus, touch or handshake with sufferers and touching the face, mouth and nose by the hands exposed to the Corona virus. Based on the results of a survey conducted by the Community Partnership Program (PKM) team in Palioi Village, Kindang District, Bulukumba Regency, it was found that there was still a lack of awareness and understanding of the community regarding Clean and Healthy Behaviors to prevent Covid-19 transmission. The targets in this Partnership Program activity were Posyandu cadre partners, they are consisting of 6 people. The methods used in the Community Partnership Program (PKM) are lectures, discussions and practice. From the Community Partnership Program (PKM), it can be concluded that Posyandu Mawar cadre partners have increased understanding and awareness in an effort to implement Clean and Healthy Behavior (PHBS) to prevent Covid-19 transmission in households and communities in Palioi Village, Kindang District, Bulukumba Regency